Analisis Hadis dalam Khanduri Laot pada Masyarakat pesisir Aceh Tamiang - Syahrizal; Haq, Zhiaul; Syahriza, Rahmi (Academy of Education Journal, 2024)
The Khaduri Laot tradition is a traditional ceremony that must be carried out by the coastal communities of Aceh Tamiang, especially at the end of the west season or before the east season. This tradition has been carried out routinely by every village under the Panglima Laot area. For the local fishing community, Khaduri Laot reflects the relationship between humans, their creator, and the surrounding environment. This ceremony is believed to have a major influence on the safety of fishermen and the blessings of marine products. Khaduri Laot is considered a cultural tradition that must be maintained and preserved. Local people's beliefs state that not carrying out this ceremony can bring disaster or danger. On the contrary, the Khaduri Laot celebration is believed to bring blessings and abundant sustenance to fishermen and coastal communities. In addition, this ritual is also believed to provide protection and security for fishermen who sail at sea. This tradition not only has a spiritual dimension, but also a cultural one in maintaining harmony between humans and nature.